2017
DOI: 10.1021/acs.inorgchem.6b00991
|View full text |Cite
|
Sign up to set email alerts
|

Spin-Polarization-Induced Preedge Transitions in the Sulfur K-Edge XAS Spectra of Open-Shell Transition-Metal Sulfates: Spectroscopic Validation of σ-Bond Electron Transfer

Abstract: Sulfur K-edge XAS spectra of the monodentate sulfate complexes [MII(itao)(SO4)(H2O)0,1] and [Cu(Me6tren)(SO4)] exhibit well-defined pre-edge transitions at 2479.4 eV, 2479.9 eV, 2478.4 eV, and 2477.7 eV, respectively (M = Co, Ni, Cu), despite having no direct metal-sulfur bond, while the XAS pre-edge of [Zn(itao)(SO4)] is featureless. The sulfur K-edge XAS of [Cu(itao)(SO4)] but not of [Cu(Me6tren)(SO4)] uniquely exhibits a weak transition at 2472.1 eV, an extraordinary 8.7 eV below the first inflection of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 73 publications
1
6
0
Order By: Relevance
“…Of the four Zn-sites, two are fully coordinated to water, and the other two bind inside the U 70 ring (Figure b). The 3d 10 electron configuration of Zn II minimizes covalent linkage to the sulfate ligands, as recently described in X-ray absorption studies . In this prior study, pre-edge features in sulfur K-edge X-ray absorption spectra were observed for sulfate complexes of Co­(II), Ni­(II), and Cu­(II) but not Zn­(II).…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…Of the four Zn-sites, two are fully coordinated to water, and the other two bind inside the U 70 ring (Figure b). The 3d 10 electron configuration of Zn II minimizes covalent linkage to the sulfate ligands, as recently described in X-ray absorption studies . In this prior study, pre-edge features in sulfur K-edge X-ray absorption spectra were observed for sulfate complexes of Co­(II), Ni­(II), and Cu­(II) but not Zn­(II).…”
Section: Resultssupporting
confidence: 56%
“…The 3d 10 electron configuration of Zn II minimizes covalent linkage to the sulfate ligands, as recently described in X-ray absorption studies. 57 In this prior study, pre-edge features in sulfur K-edge X-ray absorption spectra were observed for sulfate complexes of Co(II), Ni(II), and Cu(II) but not Zn(II). The authors attributed this to ligand (sulfate) contributions to the 3d LUMO of the divalent transition metal, which is not possible for closed-shell Zn II .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The two XAS spectra exhibit a similar rising K-edge, while the XAS of the copper complex also exhibits a very strong pre-edge feature of 0.68 normalized intensity units. Prior ligand K-edge XAS studies have shown that ligand pre-edge features most often arise from delocalization of the 3d hole of a first row transition metal into a filled ligand n p shell. ,, The pre-edge feature then reflects a vertical 1s → n p electronic transition into the newly unfilled ligand valence n p state. The intensity of the ligand pre-K-edge transition is a direct measure of ligand–metal covalency. …”
Section: Resultsmentioning
confidence: 99%
“…The 3d 10 of Zn II configuration minimizes covalent linkage of the sulfate ligands, as recent in X-ray absorption studies. 43 Small Angle X-ray Scattering. The extensive U70-Mn II -U70 and minimal U70-Zn II -U70 connectivity observed in the solid-state compounds was also evidenced upon dissolution.…”
Section: U IV -Transition Metal Assembliesmentioning
confidence: 99%